Model Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa Kelas VII Materi PLSV dan PtSLV - Muzayyanah Muzayyanah; Tri Novita Irawati; Sholahudin Al Ayubi (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to improve the learning outcomes of seventh grade students on the material of Linear Equation One Variable (PLSV) and Linear Inequality One Variable (PtSLV) through the application of the Problem Based Learning (PBL) learning model. This research is a Classroom Action Research (PTK) conducted in two cycles at Bustanul Ulum Pakusari Islamic Junior High School. Each cycle consists of planning, action, observation, and reflection stages. The results showed that in cycle I the average score of students was 69.3 with a completeness rate of 69%, while in cycle II there was an increase in the average score to 74.3 with a completeness rate of 74%. In addition, the activeness of students in the learning process increased from 76% in cycle I to 100% in cycle II. The application of the PBL model is able to increase the active involvement and learning motivation of female students, and has a positive impact on improving learning outcomes. Thus, the application of the PBL model is effective in improving the quality of mathematics learning, especially in PLSV and PtSLV material.